2008
DOI: 10.1038/onc.2008.115
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated knockdown of Pdcd4 expression causes upregulation of p21(Waf1/Cip1) expression

Abstract: The transformation suppressor gene, programmed cell death gene 4 (Pdcd4), inhibits tumor-promoter-mediated transformation of mouse keratinocytes and has been implicated as a tumor suppressor gene in the development of human cancer. The Pdcd4 protein interacts with translation initiation factors eIF4A and eIF4G and binds to RNA, suggesting that it might be involved in regulating protein translation or other aspects of RNA metabolism. To study the function of Pdcd4 in more detail, we have downregulated Pdcd4 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 59 publications
(66 reference statements)
7
88
0
Order By: Relevance
“…We have previously shown that Pdcd4 inhibits the activity of transcription factors c-Jun and p53 by interfering with their ability to cooperate with p300 (Bitomsky et al, 2004(Bitomsky et al, , 2008. While studying the effect of Pdcd4 on c-Myb, another transcription factor recruiting p300, we noted that Pdcd4 strongly decreased the amount of c-Myb generated from a cytomegalovirus (CMV) promoter-based c-Myb expression vector.…”
Section: C-myb Mrna Is a Translational Target Of Pdcd4mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that Pdcd4 inhibits the activity of transcription factors c-Jun and p53 by interfering with their ability to cooperate with p300 (Bitomsky et al, 2004(Bitomsky et al, , 2008. While studying the effect of Pdcd4 on c-Myb, another transcription factor recruiting p300, we noted that Pdcd4 strongly decreased the amount of c-Myb generated from a cytomegalovirus (CMV) promoter-based c-Myb expression vector.…”
Section: C-myb Mrna Is a Translational Target Of Pdcd4mentioning
confidence: 99%
“…Transient transfections were performed in the QT6 fibroblast line as described (Bitomsky et al, 2008). To monitor and normalize transfection efficiencies, the b-galactosidase expression plasmid CMVb (Invitrogen, Karlsruhe, Germany) was included in each transfection.…”
Section: Cells and Transfectionsmentioning
confidence: 99%
See 3 more Smart Citations